(untitled) (Journal of Engineering, 2009)
The main object of this work is to study the effect of coarse aggregate/cement ratio (A/C) on the property of no fine concrete. In this work, three ratio of A/C were used (6, 9 and 12 by weight).The cement content is maintained constant (125kg/m3) while the w/c ratio ranges from (0.39 to 0.55 by weight). Tests are carried out on hardened concrete to investigate the effect of coarse aggregate/cement ratio on the compressive strength, absorption%, density, porosity%, ultrasonic pulse velocity, acoustic impedance of mixes. The results showed that increasing the percentage of A/C ratio by weight from 6 to 12 for the used mixes reduces the compressive strength, ultrasonic pulse velocity and acoustic impedance, on the other hand the porosity and the absorption percentage, increase with increasing ratio of A/C for all studied mixes. At 28 days the compressive strength , ultrasonic pulse velocity and acoustic impedance tests with A/C ratio of (12) are (2.8.MPa), (2km/sec) and (3×106 Kg/(sec.m2)) respectively while decreasing the ratio to (6) improves these properties to (9.3MPa), (3km/sec) and ( 5.7 ×106 Kg/(sec.m2)) respectively On the other hand the porosity and the absorption % decrease with decreasing the ratio of A/C for all studied mixes . At 28 days the porosity and the absorption % with A/C ratio of (12) are (40%) and (2.7%) respectively with decreasing the ratio to 6 decrease these properties to (19%) and (1%) respectively. The densities of the mixes were tested. At 28 days the density with A/C ratio of (12) are (1512 kg/m3 )with decreasing the ratio to 6 increase the density to(1907 kg/m3 ) Based on the analysis of experimental results, several graphs and tables have been prepared to study the properties of no fine concrete